2022
DOI: 10.1002/pen.26135
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐responsive dielectric pulse in poly(vinylidene fluoride)/polyethylene glycol fibrous mats

Abstract: Thermo‐responsive dielectric materials have attracted broad attention in smart electronic device applications. Here, we present a facile one‐step fabrication technique of thermo‐responsive dielectric fibrous mats via efficient solution blow spinning of poly (vinylidene fluoride)/polyethylene glycol (PVDF/PEG). A strong room‐temperature dielectric pulse is triggered by thermally induced crystalline–amorphous phase transition of the PEG. The PVDF, serving as a host, enables the fibrous mats not only to attain so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Meanwhile, a versatile range of studies have been conducted on SMP and nanoarchitectures recently with versatile enhanced properties for multifunctional applications. [ 98–180 ]…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a versatile range of studies have been conducted on SMP and nanoarchitectures recently with versatile enhanced properties for multifunctional applications. [ 98–180 ]…”
Section: Discussionmentioning
confidence: 99%
“…The absorption peak at 1175 cm À1 represents the stretching vibrations of C F. The series of absorption peaks at 3400 cm À1 (broadband, the stretching vibration of the O H group), 2867 cm À1 (stretching vibration of C H), and 1106 cm À1 (stretching vibration of C O) are assigned to the typical characteristic bands of PEG, which are observed in the infrared spectra of all fibrous films. [24][25][26] Combining SEM, TEM, and FTIR, it can be demonstrated that PEG-PVDF coaxial nanofiber films are successfully prepared under different processing conditions.…”
Section: Morphology and Structurementioning
confidence: 99%